The arrival - Tan, Shaun, ....- (London : Hodder Children's Books, 2007)
In this wordless graphic novel, a man leaves his homeland and sets off for a new country, where he must build a new life for himself and his family.
Keywords: Migranten; Wordless Graphic Novel